Correcting sponge names: nomenclatural update of lower taxa level Porifera - Soest, Rob W.m. Van (Zootaxa, 2024)
The online World Porifera Database (WPD), the Porifera part of the World Register of Marine Species (WoRMS), lists virtually all published scientific names of sponges. The names of the WPD (as indeed all names in WoRMS) are guided by the Code of the International Comnission on Zoological Nomenclature (ICZN). The WPD names include all currently accepted as well as original combinations, and a majority of non-accepted non-original combinations. Currently, among the accepted names about 200 original lower taxa combinations were found to be accepted by default, usually varieties or formae, which were given that status in the WPD because there was no sufficient published information to support arguments for or against the accepted status. After 1961, varieties and formae are considered infrasubspecific taxa whose names are not regulated by the Code and the names are unavailable, but prior to that date these trinominal taxa are potential available names. It is the purpose of the present study to evaluate these original default ‘accepted’ combinations and arrive at an argumented judgement on whether they are to be truly accepted or non-accepted. Furthermore, additional lower taxa name violations of the Code are also included. Overall, there are three categories of names of lower taxa treated here, (1) with combinations, which are judged to be accepted with elevated status as (sub)specific taxa, (2) with combinations judged to be junior synonyms, and (3) with combinations, which are violating articles of the Code. Among the last category there are a small number of varietal taxa described after the 1960 cut-off date, which are unavailable but are proposed to have the original name combination retained, but as new names with authorship and year changed to those of the present article. Also, names found to be unavailable for various reasons (four-name combinations, junior homonyms, phylocode names) are in this category. The following 31 new names are proposed (three of which are junior synonyms of senior accepted names, and an additional three are unavailable names made available by employing the same name combination with the present authorship and year): Aaptos hoshinoi nom.nov., Ancorina nanosclera nom.nov., Axinella kurushima nom.nov., Callyspongia (Cladochalina) desqueyrouxfaundezae nom.nov., Cliona carpenteri subsp. hentscheli nom.nov., Callyspongia (Toxochalina) gustavoi nom.nov., Craniella microspira nom.nov., Dictyaulus romani nom.nov., Grantia breitfussi nom.nov., Haliclona alba subsp. albapontica nom.nov., Haliclona aquaeductus subsp. sebastopolensis nom.nov., Haliclona inflata subsp. vladimiri nom.nov., Haliclona informis subsp. voldomaroi nom.nov., Haliclona palmata subsp. pontuseuxiniensis nom.nov., Haliclona (Gellius) arthuri nom.nov., Haliclona (Gellius) godthaabae nom.nov., Haliclona merguiensis nom.nov., Haliclona senjitanitai nom.nov., Iophon hentscheli nom.nov., Leucandra wilsoni nom.nov., Paraleucilla bassensis nom.nov. (= P. saccharata), Pione carpenteri subsp. hentscheli nom.nov., Psammocinia samaaii nom.nov., Protoschmidtia czerniavskyi nom.nov. (= Metschnikowia tuberculata), Reiswiginella nom.nov., Scalarispongia lamarcki nom.nov., Spheciospongia hentscheli nom.nov., Spongia (Spongia) vonlendenfeldi nom.nov. (= S. (S.) lignosa), Suberites austral nom.nov., Suberites dendyi nom.nov., Suberites simae nom.nov., and Timea levii nom.nov.